2014
DOI: 10.1021/ie5015525
|View full text |Cite
|
Sign up to set email alerts
|

Natural Gas Steam Reforming over Rhodium/Alumina Catalysts: Experimental and Numerical Study of the Carbon Deposition from Ethylene and Carbon Monoxide

Abstract: Natural gas steam reforming (SR) over technically used rhodium/alumina (Rh/Al 2 O 3 ) honeycomb catalysts is studied experimentally at temperatures between 923 and 1073 K and steam-to-carbon ratios (S/C) of unity, with regard to coke deposition caused by the decomposition of the product species ethylene (C 2 H 4 ) and carbon monoxide (CO). Furthermore, the process is modeled using detailed reaction mechanisms, and numerical simulations are carried out to describe the coke formation on Rh/Al 2 O 3 catalysts qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The surface species chemisorption enthalpies are calculated via the UBI-QEP method [93][94][95]. This methodology is extensively applied in fundamental microkinetic modeling studies [41,[96][97][98][99][100][101] to relate the surface species chemisorption enthalpies to atomic chemisorption enthalpies. In this work, the latter are the chemisorption enthalpies of H, C and O, which are considered as three additional adjustable model parameters.…”
Section: Rate Coefficientsmentioning
confidence: 99%
“…The surface species chemisorption enthalpies are calculated via the UBI-QEP method [93][94][95]. This methodology is extensively applied in fundamental microkinetic modeling studies [41,[96][97][98][99][100][101] to relate the surface species chemisorption enthalpies to atomic chemisorption enthalpies. In this work, the latter are the chemisorption enthalpies of H, C and O, which are considered as three additional adjustable model parameters.…”
Section: Rate Coefficientsmentioning
confidence: 99%
“…Several authors ( Rostrup-Nielsen 1972, 1984, Jankhah et al 2008, Cimenti and Hill 2009, Essmann et al 2014 highlighted that both the thermodynamic equilibrium conditions and the kinetic rate of all reactions and phase transitions should be considered in predictions of carbon deposits. However, Rostrup-Nielsen and Christiansen (2011) showed that the equilibrium constants for methane decomposition decisively depend on the metal catalyst type and stated that "[t]he important question is whether or not carbon is formed and not the rate at which it may be formed."…”
Section: Carbon Depositsmentioning
confidence: 99%
“…Chemisorption enthalpies for the various surface species are calculated via the UBI-QEP method [27][28][29], which is widely used in fundamental microkinetic modeling studies [70][71][72][73][74][75][76][77]. This method relates the chemisorption enthalpy of a species to the atomic chemisorption enthalpies of H, C and O.…”
Section: Reaction Rate Expression Single-event Microkinetics and Thementioning
confidence: 99%